2016
DOI: 10.1111/cfs.12268
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and correlates of co‐occurrence among multiple types of child maltreatment

Abstract: This study examined the patterns and correlates of the types of maltreatment experienced by adolescents aged 9–12, participating in an ongoing longitudinal study on the impact of neglect on children’s development. Using case record abstraction, the study compared the child protection classification and findings from the case record abstraction with regard to the rates of four types of maltreatment (i.e. physical, sexual, emotional abuse and neglect) as well as co-occurrence across multiple types of maltreatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 32 publications
2
77
2
Order By: Relevance
“…The severity of the abuse and neglect experienced by 82% of the children and the multiple types of maltreatment experienced by over 70% of them suggests that thresholds for the use of CPPs and for placement in OHC were high in the case study authority. Although maltreatment severity has been investigated in the USA and high rates of poly-victimisation have been reported there, these issues have received barely any attention in the UK (Finkelhor et al, 2007, Pears et al, 2008, Wade et al, 2011, Kim et al, 2016, Radford et al, 2013, Cecil et al, 2017). The greater likelihood that children ever in care had experienced high severity maltreatment (88%) compared to those never in care (74%) suggests, as we might anticipate, that the threshold for placing children away from home was even higher than that for CPPs.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of the abuse and neglect experienced by 82% of the children and the multiple types of maltreatment experienced by over 70% of them suggests that thresholds for the use of CPPs and for placement in OHC were high in the case study authority. Although maltreatment severity has been investigated in the USA and high rates of poly-victimisation have been reported there, these issues have received barely any attention in the UK (Finkelhor et al, 2007, Pears et al, 2008, Wade et al, 2011, Kim et al, 2016, Radford et al, 2013, Cecil et al, 2017). The greater likelihood that children ever in care had experienced high severity maltreatment (88%) compared to those never in care (74%) suggests, as we might anticipate, that the threshold for placing children away from home was even higher than that for CPPs.…”
Section: Discussionmentioning
confidence: 99%
“…The number of maltreatment subtypes children have experienced relates to poorer emotional and behavioral symptoms (Kim, Cicchetti, Rogosch, & Manly, 2009) and biological measures, including hypercortisolism (Cicchetti & Rogosch, 2001, 2007). A recent study found that co-occurring neglect, emotional maltreatment, and physical abuse was the most common presentation of maltreatment in CPS records (Kim, Mennen, & Trickett, 2016). Pure subtypes of maltreatment, therefore, are not the norm, and children who experience multiple subtypes are at increased risk for a range of adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study examining the correlations among types of maltreatment shows that some classifications underestimate the co-occurrence indexes among the several types of maltreatment. This indicates it is common and that the physical and emotional abuse were the subtypes with higher rate of concomitance ( 70 ). In this sense, the official classification may neither represent the experience as accurately as expected in the case of children victims of abuse nor take the several types of maltreatment into account.…”
Section: Discussionmentioning
confidence: 99%